Preparation and application of indolo-indolo-quinoxaline-phenazine MR-TADF blue-light-emitting material

By designing a new MR-TADF blue light luminescent material, using indoleoindolequinoxaline[3,2,1-kl]phenazine framework and multiple groups to modify it, the quantum efficiency of existing materials in OLEDs applications is solved. The problem of insufficient color purity achieves high efficiency and high color purity narrowband blue light emission, and improves the thermal stability and carrier transmission performance of the material.

CN119462674AActive Publication Date: 2025-02-18CHANGZHOU UNIV

Patent Information

Application Number
CN202411866764.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-02-18
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

The existing MR-TADF blue light materials have not yet been optimized in OLEDs applications, and the thermal stability and carrier transmission performance need to be further improved.

Method used

A new type of MR-TADF blue light luminescent material was designed, using indoleoindolequinoxaline[3,2,1-kl]phenazine as a rigid planar framework, and passed through tert-butyl, toluene, N,N- Groups such as dianiline modify four chemical sites to construct a narrow band emission material with multiple resonance effects.

Benefits of technology

The narrow spectrum band of MR-TADF blue light luminescent material has been achieved with high efficiency luminescence, with an external quantum efficiency of 15.2%, high color purity, good thermal stability of the material and excellent carrier transmission performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462674A_ABST
    Figure CN119462674A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of organic photoelectric materials, and particularly relates to preparation and application of an indolo-indole quinoxaline phenazine MR-TADF blue light material. The material has a rigid large-plane skeleton and is modified by a plurality of chemical sites, and efficient and narrow-spectrum blue light emission of the material can be realized by simply regulating and controlling a peripheral hooking group. The blue-light-doped electroluminescent device prepared by the method has the advantages that the blue-light-doped electroluminescent device prepared by the aid of the method has the advantages that the blue-light-doped electroluminescent device prepared by the aid of the method is high in light emitting efficiency, the thermal decomposition temperature can reach 426.1 DEG C, the blue-light-doped electroluminescent device is excellent in thermal stability, the maximum photoluminescence emission peak in methylbenzene solution is 458 nm, the half-peak width of the blue-light-doped electroluminescent device is 40 nm, the fluorescence quantum efficiency of the blue-light-doped electroluminescent device is 78.2%, the maximum emission peak of the obtained blue-light-doped electroluminescent device is 468 nm, color coordinates of the blue-light-doped electroluminescent device are (0.15 and 0.25), and the corresponding maximum external quantum efficiency The MR-TADF blue light-emitting material with an innovative structure and multiple expandability has an attractive application prospect. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of luminescent materials, and specifically relates to the preparation of a class of indole-indolequinoxaline-phenazine MR-TADF blue light materials and their application in organic electroluminescent devices (OLEDs). Background Art

[0002] Since T. Ikuta's research group first reported the thermally activated delayed fluorescence (TADF) material induced by the multiple resonance (MR) effect in 2016 (Advanced Materials, 2016, 28, 2777-2781), this type of material has been widely studied in the fields of OLEDs due to its narrow-band emission, high luminescence quantum efficiency (PLQY) and small Stokes shift in solvents of different polarities.

[0003] MR-TADF material molecules usually have a planar and rigid polycyclic aromatic heterocyclic structure. The heteroatoms interrupt the electron cloud distribution of the molecule, thereby inducing a multiple resonance effect between the complementary conjugation effects of the heteroatoms, inducing the alternating positioning of the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) on adjacent atoms, which not only produces a smaller ΔE ST , realizing the TADF characteristics, and producing a shallow potential energy surface, thus achieving a unique narrow-band emission (FWHM < 50 nm). When the molecule is excited to the singlet state or radiatively transitions back to the ground state, its electron cloud density will produce short-range charge transfer (SRCT) between adjacent atoms. This special SRCT method is different from the intramolecular charge transfer (ICT) method of traditional DA-type TADF. Instead, it is similar to a localized excitation (LE), which maintains the electron-hole overlap and enables the MR-TADF material to obtain a larger oscillator strength, which helps to improve the photoluminescence quantum yield (PLQY) and radiative transition rate. In addition, SRCT also helps to eliminate the spectral fine structure of LE emission caused by the highly conjugated structure, making the luminescence spectrum of the MR-TADF material smoother and further improving the luminescence color purity.

[0004] In 2019, Shuit-Tong Lee reported blue light OLEDs based on the MR-TADF material quinolinone [3,2,1-de]acridine-5,9-dione as the active layer, with a maximum external quantum efficiency of 19.4% and a half-width of 39 nm (Adv. Optical Mater. 2019, 1801536); in 2024, Wang Lixiang's research group used the MR-TADF material 5tCzPPm as a sensitizer and obtained a solution-based deep blue light OLED with a maximum external quantum efficiency of 15.6, showing the potential application prospects of MR-TADF materials in OLEDs. Summary of the invention

[0005] In order to overcome the shortcomings of the prior art, the present invention designs a class of organic blue light emitting materials with MR-TADF characteristic narrow-band emission, and utilizes the synergistic effect of MR narrow-band emission and TADF efficient luminescence to achieve narrow-band efficient luminescence of MR-TADF blue light emitting materials and their application in organic electroluminescent diodes.

[0006] The present invention provides a novel MR-TADF blue light emitting material using indole indolequinoxaline [3,2,1-kl] phenazine as a rigid planar skeleton and modifying four chemical sites with groups such as tert-butyl, toluene, N,N-diphenylamine, carbazole, 3,6-di-tert-butylcarbazole, and N,N-dimethylaniline.

[0007] The present invention provides a type of MR-TADF blue light emitting material having a structure shown in Formula I:

[0008] Formula I Wherein: the R units are independently selected from any one of the following formula II:

[0009] Formula II.

[0010] The specific structure of the preferred MR-TADF blue light emitting material is shown in Formula III, and these compounds are only representative compounds:

[0011] Formula III.

[0012] The R unit in the more preferred MR-TADF blue light emitting material is tert-butyl, and the molecular structure is as follows, named DtBuCzN: .

[0013] The preparation steps of MR-TADF blue light emitting material DtBuCzN are as follows: Using 1-bromo-3,6-di-tert-butyl-9-H-ylcarbazole and 1,3-difluoro-3-nitrobenzene as raw materials, the target compound is obtained through Ullmann reaction, nitro reduction reaction and Buchwald-Hartwig reaction. The specific steps include: (1) dissolving 3,6-di-tert-butyl-9H-carbazole, 2,6-difluoronitrobenzene and potassium phosphate in N,N-dimethylformamide, and subjecting the mixture to reflux reaction for 10-12 h. After the reaction is completed, separating and purifying the mixture to obtain compound M1; the molar ratio of 3,6-di-tert-butyl-9H-carbazole, 2,6-difluoronitrobenzene and potassium phosphate is 100-105:35-40:155-160; (2) dissolving compound M1 in dichloromethane, adding liquid bromine dropwise in an ice bath, stirring to react for 10-12 h, and after the reaction is completed, separating and purifying to obtain compound M2; the molar ratio of the liquid bromine to compound M1 is 2-2.2:1; (3) Compound M2 and stannous chloride were dissolved in chloroform, refluxed for 2 h, the reaction was stopped, and compound M3 was obtained by separation and purification; wherein the molar ratio of compound M2 to stannous chloride was 1:15; (4) The palladium catalyst tri(dibenzylideneacetone)dipalladium and sodium cyanide were dissolved in toluene. Under N2 protection, a xylene solution of compound M3 was added and the mixture was heated to 110-120°C and refluxed for 15-16 h. The target compound was separated and purified to obtain the target compound.

[0014] The present invention also provides an application of the MR-TADF blue light emitting material, which is used as a light emitting layer material of an organic electroluminescent diode for an organic electroluminescent diode.

[0015] The structure of the blue light emitting OLED device of the present invention is: ITO / PEDOT:PSS (30nm) / mCPCN:x wt%MR-TADF (25nm) / TmPyPB (50nm) / LiF (1nm) / Al (120nm).

[0016] Among them, ITO is indium tin oxide conductive glass, which serves as a substrate and anode; PEDOT:PSS is a hole injection layer; mCPCN is a main material of the light-emitting layer, MR-TADF is a blue light material of the present invention, which serves as a guest material of the light-emitting layer; TmPyPB is an electron transport layer, LiF is an electron injection layer, and Al is a cathode. Among them, x=1-10.

[0017] In the preferred application method, the MR-TADF blue light emitting material DtBuCzN is used to prepare the light-emitting layer of the blue light OLEDs device, and a blue light OLEDs device with a maximum emission peak at 468 nm blue light electroluminescence and an external quantum efficiency of up to 15.2% is obtained.

[0018] Compared with the existing technology, the beneficial effects of the present invention are: (1) The molecules of the MR-TADF blue light emitting material of the present invention have a planar multi-nitrogen heteroatom structure. The molecular structure of the material is innovative and has multi-site modification, which can enrich the library of organic MR-TADF blue light emitting materials.

[0019] (2) The organic blue light emitting material of the present invention has a significant MR-TADF effect, high luminous efficiency and high color purity, creating conditions for high-definition display.

[0020] (3) This type of MR-TADF blue light organic luminescent small molecule material has high thermal stability and excellent carrier transport performance.

[0021] (4) The MR-TADF blue light organic light emitting material of the present invention can be used as a light emitting layer material and applied to a blue light OLEDs device. The preferred embodiment of the present invention realizes blue light emission of the OLEDs device and obtains excellent external quantum efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the H NMR spectrum of the compound DtBuCzN prepared in Example 1 of the present invention.

[0023] Figure 2 This is the mass spectrum of the compound DtBuCzN prepared in Example 1 of the present invention.

[0024] Figure 3 Schematic diagram of the single crystal diffraction structure of the compound DtBuCzN prepared in Example 1 of the present invention.

[0025] Figure 4 This is a thermal gravimetric curve of the solid powder of the compound DtBuCzN prepared in Example 1 of the present invention.

[0026] Figure 5 The compound DtBuCzN prepared in Example 1 of the present invention is 10 -5 UV-visible absorption spectrum of 1.5 mol / L concentration toluene solution.

[0027] Figure 6 The compound DtBuCzN prepared in Example 1 of the present invention is 10 -5 Photoluminescence spectrum in mol / L concentration toluene solution.

[0028] Figure 7 The compound DtBuCzN prepared in Example 1 of the present invention was dissolved in toluene solution (10 -5 mol / l) at 77 K (λ ex= 340 nm).

[0029] Figure 8 The compound DtBuCzN prepared in Example 1 of the present invention is 10 -5 Photoluminescence spectrum in mol / L concentration solution.

[0030] Fig. 9 The compound DtBuCzN prepared in Example 1 of the present invention was dissolved in a deoxygenated acetonitrile solution (0.1 M) with a platinum electrode as the working electrode, a platinum wire as the counter electrode, and a silver electrode as the reference electrode. + ) is used to draw the cyclic voltammetry curve of the internal standard compound.

[0031] Fig.10 This is a graph of the instantaneous lifetime of the compound DtBuCzN prepared in Example 1 of the present invention doped in an mCP film at a mass ratio of 1 wt%.

[0032] Fig.11 Schematic diagram of device energy levels of an electroluminescent device made with a doped light-emitting layer of the compound DtBuCzN prepared in Example 1 of the present invention.

[0033] Fig.12 This is an electroluminescence spectrum of the compound DtBuCzN prepared in Example 1 of the present invention doped into the mCPCN host at a mass ratio of 1 wt%.

[0034] Fig.13 This is a color coordinate diagram of a device obtained by doping the compound DtBuCzN obtained in Example 1 of the present invention into an mCPCN host at a mass ratio of 1 wt %.

[0035] Fig.14 This is a graph showing the maximum external quantum efficiency and brightness of a device obtained by doping the compound DtBuCzN prepared in Example 1 of the present invention into an mCPCN host at a mass ratio of 1 wt %. DETAILED DESCRIPTION

[0036] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments and drawings. It should be understood by those skilled in the art that the specific contents described below are illustrative rather than restrictive, and the protection scope of the present invention cannot be limited thereby.

[0037] In the present invention, the preparation methods are conventional methods unless otherwise specified, and the raw materials used can be obtained from public commercial channels unless otherwise specified. Example 1

[0038] The synthesis scheme of the indole indolequinoxaline [3,2,1-kl] phenazine material DtBuCzN is as follows, wherein all reagents such as 3,6-di-tert-butylcarbazole and 2,6-difluoronitrobenzene were purchased from Biter Pharmaceutical Reagents Co., Ltd.:

[0039] Synthetic route of compound DtBuCzN Synthesis of compound M1 In a 250 mL two-necked bottle, 3,6-di-tert-butyl-9H-carbazole (28.5 g, 102.0 mmol), 2,6-difluoronitrobenzene (6.0 g, 37.0 mmol), potassium phosphate (33 g, 156 mmol) and 120 mL of N,N-dimethylformamide (DMF) were added and refluxed for 10 h. After the reaction was completed, the reaction mixture was cooled to room temperature, the organic solvent was removed by vacuum distillation, and the mixture was extracted three times with dichloromethane, dried over anhydrous magnesium sulfate, filtered, and the filtrate was concentrated by vacuum distillation. The crude product was separated by silica gel column chromatography to obtain 1.14 g of light yellow powder M1 (11.4 g, 36.86%). 1 H NMR (400 MHz, CDCl3) δ8.10 (s, 4H), 7.85 (t, J = 8.0 Hz, 1H), 7.67 (d, J = 8.0 Hz, 2H), 7.48 (dd, J= 8.6, 1.7 Hz, 4H), 7.18 (d, J = 8.6 Hz, 4H), 1.45 (s, 36H). Synthesis of compound M2 In a 100 mL two-necked flask, add M1 (6.9 g, 10.2 mmol) and 50 mL of dichloromethane, add liquid bromine (3.5 g, 22.4 mmol) dropwise under ice bath, and stir for 10 h. After the reaction is completed, cool the reaction mixture to room temperature, quench the reaction with saturated sodium thiosulfate aqueous solution, extract three times with dichloromethane, dry over anhydrous magnesium sulfate, filter, and then concentrate the filtrate by vacuum distillation. The crude product is separated by silica gel column chromatography to obtain yellow powder M2 (5.0 g, 58.87%). 1H NMR (400MHz, CD2Cl2) δ = 8.03 (d, J = 4.7 Hz, 4H), 7.78 – 7.71 (m, 1H), 7.64 (d, J =7.9 Hz, 2H), 7.57 (s, 2H), 7.46 (d, J = 9.9 Hz, 2H), 7.05 (d, J = 8.6 Hz, 2H), 1.36 (d, J = 2.2 Hz, 36H). Synthesis of Compound M3 Compound M2 (1.14 g, 1.364 mmol), stannous chloride (1.338 g, 20.46 mmol) and 40 mL of chloroform solution were added to a 100 mL two-necked bottle, and the mixture was refluxed for 2 h. The reaction was stopped and then extracted with ethyl acetate. The organic layer was separated and dried over anhydrous magnesium sulfate. The filtrate was concentrated by vacuum distillation to obtain an orange solid powder. The crude product was separated by silica gel column chromatography to obtain 800 mg of light orange powder M3 (800 mg, 73.02%). 1 H NMR (400 MHz, DMSO): δ =8.32 (d, J = 17.7 Hz, 4H), 7.57 (s, 2H), 7.53 – 7.48 (m, 2H), 7.33 (d, J =2.4 Hz, 2H), 7.31 (s, 1H), 7.15 (d, J = 7.8 Hz, 1H), 7.09 (d, J = 8.6 Hz, 2H), 6.95 (s, 1H), 1.42 (d, J = 5.0 Hz, 36H). Synthesis of Compound DtBuCzN In a 50 mL double-necked flask, Pd2(dba)3 (39.5 mg, 0.043 mmol), sodium hydride (44.78 mg, 1.866 mmol) and 10 mL toluene (Tol) solution were added. Under N2 protection, 15 mL xylene solution of compound M3 (500 mg, 0.622 mmol) was added to the reaction solution, and then heated to 110 °C for reaction and reflux for 15 h. Solid impurities that were intolerant to organic solvents were removed by vacuum distillation to remove the m-xylene solution. The remaining solid was dissolved in dichloromethane. The collected organic layer was dried and the solvent was dried in turn. The crude product was separated by silica gel column chromatography to obtain orange-yellow powder DtBuCzN (318 mg, 79.39%). 1HNMR (400 MHz, CD2Cl2) δ = 8.05 (d, J = 9.2 Hz, 4H), 7.79 – 7.71 (m, 1H), 7.64(d, J = 7.7 Hz, 2H), 7.57 (s, 2H), 7.46 (d, J = 8.7 Hz, 2H), 7.05 (d, J = 8.6Hz, 2H), 1.36 (t, J = 2.0 Hz, 36H). MS(TOF-MS): m / z calcd. for C 46 H 49 N3:643.92; [MH] + found: 643.39. Example 2

[0040] The compound DtBuCzN of Example 1 was dissolved in CD2Cl2 reagent, and its nuclear magnetic resonance hydrogen spectrum was measured using a 400 MHz nuclear magnetic resonance spectrometer. Figure 1 shown. Example 3

[0041] The molecular weight of the compound DtBuCzN was tested by time-of-flight mass spectrometry, and its mass spectrum is shown in Figure 2 The theoretical molecular weight of the compound DtBuCzN is 643.92, and the molecular weight obtained by mass spectrometry is 643.39. Obviously, the molecular weight of the compound is accurate. Example 4

[0042] The compound DtBuCzN of Example 1 was dissolved in chloroform as a good solvent and ethanol as a poor solvent, and DtBuCzN single crystals were grown at room temperature by solvent diffusion method, and then their exact geometric shapes were determined by single crystal X-ray diffractometer (XRD), such as Figure 3 shown. Example 5

[0043] The thermal stability of the compound DtBuCzN prepared in Example 1 was tested. In a nitrogen atmosphere, the compound was heated from room temperature to 700°C at a heating rate of 20°C / min and a thermal weight loss test was performed. Figure 4 As shown, the temperature at which the compound DtBuCzN loses 5% of its weight is 425.5 °C, indicating that the material has good thermal stability, laying the foundation for the subsequent solution processing of the material as a light-emitting layer and the preparation of fully evaporated devices. Example 6

[0044] The compound DtBuCzN in Example 1 was dissolved in a toluene solution (10 -5M), and measured the UV-visible absorption spectrum of the compound DtBuCzN toluene solution at room temperature. Figure 5 It can be seen that the strong absorption band in the range of 280 nm to 300 nm originates from the π-π* transition within the molecule, showing a strong and sharp absorption peak at 436 nm, which is attributed to the transition absorption of short-range charge transfer of the entire rigid molecular structure. Example 7

[0045] The compound DtBuCzN in Example 1 was dissolved in a toluene solution (10 -5 M), the photoluminescence spectrum of the compound DtBuCzN toluene solution at room temperature was measured. Figure 6 It can be seen that the compound shows a strong and sharp emission peak at 458 nm, which is blue light emission, and its half-peak width is 40 nm. Example 8

[0046] The compound DtBuCzN in Example 1 was made into a thin film on a glass substrate, and the fluorescence spectrum (Fl) and phosphorescence spectrum (Ph) of the compound DtBuCzN in a pure film state at 77K were tested. Figure 7 As shown. Both the low-temperature fluorescence and low-temperature phosphorescence spectra show broad peaks without fine structures, which also means that they are generated by intramolecular charge transfer. According to the peak positions of the low-temperature fluorescence and phosphorescence spectra and the formula E = 1240 / λ, it can be estimated that the S1 and T1 energy levels of the compound DtBuCzN are 2.84 eV and 2.48 eV, respectively, and ΔE ST is 0.36 eV. Example 9

[0047] The compound DtBuCzN in Example 1 was dissolved in n-hexane, toluene, ether, dioxane, tetrahydrofuran, dichloromethane, acetone, N,N-dimethylformamide and ethyl acetate solutions (10 -5 M), test its photoluminescence spectra in different solutions, such as Figure 8 It is found that the compounds have similar luminescence spectra. With the increase of solvent polarity, the compounds show a weak solvation effect and the Stokes shift is not obvious, which is a typical characteristic of compounds with multiple resonance effect thermally activated delayed fluorescence (MR-TADF). Example 10

[0048] The electrochemical performance test conditions of the compound DtBuCzN in Example 1 are as follows: the prepared compound DtBuCzN is placed in a deoxygenated acetonitrile solution (0.1 M) with a platinum electrode as the working electrode, a platinum wire as the counter electrode, a silver electrode as the reference electrode, and ferrocene (Fc / Fc + ) was used as the internal standard compound for testing. Fig. 9 As shown in the figure, the compound DtBuCzN exhibits an irreversible oxidation peak in the range of 0-0.7 V. According to the empirical formula, the HOMO energy level of the compound can be calculated to be -4.69 eV. Combined with the peak position of the blue absorption spectrum of the pure film of the compound, the band gap (E g ) is 2.75 eV, and its LUMO is calculated to be -1.94 eV. Embodiment 11

[0049] The photoluminescence quantum efficiency (PLQY) test of the compound DtBuCzN in Example 1 was completed in a transient fluorescence photometer equipped with an integrating sphere. The test method is as follows: the compound is made into a 0.1 wt% doped sample film of mCP, and the fluorescence intensity of the blank quartz sheet and the sample film is tested successively. The fluorescence quantum efficiency (PLQY) of the compound is calculated to be 78.2%. Example 12

[0050] The instantaneous lifetime of the compound DtBuCzN in Example 1 was tested in a 0.1% doped mCP film under nitrogen atmosphere by FlS1000. Fig.10 As shown, the delayed lifetime of the compound DtBuCzN is 31.4 µs after fitting. According to the half-peak width of the material in Example 7 of 40 nm and the ΔE of the material obtained by the test in Example 8, ST It is 0.36 eV, indicating that the compound DtBuCzN has MR-TADF characteristics. Example 13

[0051] The application of the compound DtBuCzN in Example 1 in an organic electroluminescent device. The compound is used as a guest material of the light-emitting layer to prepare an organic electroluminescent diode having a structure of ITO / PEDOT:PSS(30 nm) / mCPCN: compound DtBuCzN (25 nm)(25 nm) / TmPyPB(50 nm) / LiF(1 nm) / Al(120 nm). Among them, PEDOT:PSS is a hole injection layer, mCPCN is a main material of the light-emitting layer, TmPyPB is an electron transport layer, LiF is an electron injection layer, and Al is a cathode. Fig.11 shown. Embodiment 14

[0052] The electroluminescence spectrum of the compound DtBuCzN in Example 1 in an organic electroluminescent device is as follows: Fig.12 As shown, at a doping concentration of 1 wt%, the electroluminescent device shows blue light emission, and the maximum emission peak of the doped device is located at 468 nm. Embodiment 15

[0053] The color coordinates of the electroluminescent device of the compound DtBuCzN in Example 1 at a doping concentration of 1 wt% are as follows: Fig.13 As shown, the corresponding color coordinate values ​​are (0.15, 0.25). Example 16

[0054] The external quantum-brightness curve of the compound DtBuCzN in Example 1 in the organic electroluminescent device is as follows: Fig.14 As shown in the figure, at a doping concentration of 1 wt%, the maximum external quantum efficiency of the doped device is 15.2%.

[0055] Although the present invention has been described in conjunction with the preferred embodiments, the present invention is not limited to the above embodiments, and it should be understood that the appended claims summarize the scope of the present invention. Under the guidance of the inventive concept, those skilled in the art should be aware that certain changes made to the various embodiments of the present invention will be covered by the spirit and scope of the claims of the present invention.

Claims

1. A type of indole-indolequinoxaline-phenazine MR-TADF blue light material, characterized in that: The luminescent material has a molecular structure shown in Formula I: , Formula I Wherein: the R units are independently selected from any one of the following: 。 2. The indole indolequinoxaline phenazine MR-TADF blue light material according to claim 1, characterized in that: The molecular structural formula of the MR-TADF blue light material is any one of the following: 。 3. The method for preparing the indole indolequinoxaline phenazine MR-TADF blue light material according to claim 1, characterized in that: Using 1-bromo-3,6-di-tert-butyl-9-H-ylcarbazole and 1,3-difluoro-3-nitrobenzene as raw materials, the target compound was obtained through Ullmann reaction, nitro reduction reaction and Buchwald-Hartwig reaction.

4. The method for preparing the indole indolequinoxaline phenazine MR-TADF blue light material according to claim 3, characterized in that: The steps include: (1) dissolving 3,6-di-tert-butyl-9H-carbazole, 2,6-difluoronitrobenzene and potassium phosphate in N,N-dimethylformamide, and subjecting the mixture to reflux reaction for 10-12 h. After the reaction is completed, separating and purifying the mixture to obtain compound M1; the molar ratio of 3,6-di-tert-butyl-9H-carbazole, 2,6-difluoronitrobenzene and potassium phosphate is 100-105:35-40:155-160; (2) dissolving compound M1 in dichloromethane, adding liquid bromine dropwise in an ice bath, stirring to react for 10-12 h, and after the reaction is completed, separating and purifying to obtain compound M2; the molar ratio of the liquid bromine to compound M1 is 2-2.2:1; (3) Compound M2 and stannous chloride were dissolved in chloroform, refluxed for 2 h, the reaction was stopped, and compound M3 was obtained by separation and purification; wherein the molar ratio of compound M2 to stannous chloride was 1:15; (4) Dissolve the palladium catalyst and sodium cyanide in toluene, add the xylene solution of compound M3 under N2 protection, heat to 110-120 °C, reflux for 15-16 h, separate and purify to obtain the target compound; the palladium catalyst is tris(dibenzylideneacetone)dipalladium.

5. The use of the indole indolequinoxaline phenazine MR-TADF blue light material according to claim 1, characterized in that: The MR-TADF blue light emitting material is used as a blue light emitting material of a light emitting layer in an organic electroluminescent device.

6. The use of the indole indolequinoxaline phenazine MR-TADF blue light material according to claim 5, characterized in that: The MR-TADF blue light material is used as a guest material of a light-emitting layer in an organic electroluminescent device.

7. The use of the indole indolequinoxaline phenazine MR-TADF blue light material according to claim 6, characterized in that: The doping amount of the MR-TADF blue light material is 1-10 wt%.

8. The use of the indole indolequinoxaline phenazine MR-TADF blue light material according to any one of claims 5 to 6, characterized in that: The structure of the organic electroluminescent device is ITO / PEDOT:PSS / mCPCN:x wt%MR-TADF / TmPyPB / LiF / Al; wherein ITO is indium tin oxide conductive glass, serving as a substrate and anode; PEDOT:PSS is a hole injection layer; mCPCN is a main material of the light-emitting layer; MR-TADF is the indole-indolequinoxaline-phenazine MR-TADF blue light material described in claim 1; TmPyPB is an electron transport layer; LiF is an electron injection layer, and Al is a cathode.

Citation Information

Patent Citations

  • Nitrogen-containing fused ring organic compound and application thereof

    CN110759925A

  • Nitrogen-containing heterocyclic compound, high polymer, mixture, composition and use thereof

    CN111344289A

  • Compound, organic electronic device comprising same, and display device or lighting device

    CN111620890A

  • N-containing fused ring compound and application thereof in organic electronic device

    CN112778309A

  • Anti-Kasha rule narrow-band blue-violet light TADF material and application thereof in OLEDs

    CN116535431A

Cited By

  • Organic near-infrared II-region luminescent material based on 3-oxo-3H-benzanthracene-1, 2-dinitrile as well as preparation method and application of organic near-infrared II-region luminescent material

    CN122444751A